Influence of Material Change of a Single-stage Front Gearbox Drive Shaft on Selected Strength Analysis Parameters - Podaril, Martin; Majernik, Jan (Manufacturing Technology Journal, 2018)
Contribution is focused on the analysis of power ratios on a drive shaft of a single-stage front gearbox and comparison of design solution of drive shaft using selected materials suitable for shaft production in terms of minimizing gearbox dimensions with respect to maintaining the transmitted power. The aim of the authors is to achieve the smallest possible dimensions of the gearbox shaft by changing the materials from which it is made.
Keywords: gearbox; drive shaft; material; power